Identifikasi Keanekaragaman Jenis Burung di Kawasan Kampus UIN Sultan Aji Muhammad Idris Samarinda Kalimantan Timur - Muhamad Agil; Miranda; Nafla Maulida; Muhammad Subhan Nur Pratamaullah (Biotropic : The Journal of Tropical Biology, 2024)
The State Islamic University of Sultan Aji Muhammad Idris (UINSI) Samarinda is a state Islamic campus in East Kalimantan that has good vegetation conditions so there are various types of birds in the area. This research aims to know the different kinds of bird that exist in the region of UINSI Samarinda Campus so as to be a first step towards conservation efforts. The method used in this study is Point Count by observing birds at a specified location. The bird identification was done with the help of MacKinnon's books. The data obtained was analyzed by the diversity index (H’), the relative abundance index (IKR), the redness index (E), the richness index of the species and its conservation status. The results of the study obtained 16 species of birds that are known to have one species endemic to Kalimantan, namely Lonchura fuscans. The analysis of the bird's H’ value of 2.19, the highest IKR is Passer montanus of 25.89%, the E value of 0.76, and the species richness index of 3.22. In addition, the conservation status of the birds found is 14 species of birds with Least Concern status (LC), one Vulnerable status (VU) and one Endangered status. (EN).